Biological, Environmental, and Behavioural Determinants of Human Secondary Sex Ratio: A Systematic Literature Review and Critical Medical Analysis - Pardomuan Robinson Sihombing (Awatara Publisher, 2026)
Introduction: This study presents a Systematic Literature Review to evaluate the medical validity of pre-conception interventions and environmental factors claimed to influence the secondary sex ratio (SSR). Amidst the persistence of popular but controversial sex selection methods, alongside strong cultural preferences for certain genders in various Indonesian ethnic groups, there is a clinical urgency to separate myth from valid biological mechanisms. Methods: Following the PRISMA 2020 guidelines, a comprehensive search of the PubMed and Scopus databases filtered 1,495 articles into 25 high-quality primary studies. The analysis focused on the validity of methods involving timing of sexual intercourse, physical position, dietary manipulation, vaginal pH environment, and the impact of parental stress. Results: The synthesis of evidence shows no empirical support for the effectiveness of timing coitus or sleeping on one's side in influencing sex. Conversely, the data support a variant of the Trivers-Willard Hypothesis, in which high maternal energy status correlates with male births, while chronic maternal stress and paternal toxic exposure suppress the ratio. Paradoxical findings emerge regarding paternal stress, where paternal anxiety correlates with increased male births. Conclusion: This report provides an evidence base for practitioners to deliver ethical, science-based pre-conception education.